2005
DOI: 10.1080/02770900500214783
|View full text |Cite
|
Sign up to set email alerts
|

Length of Stay and Costs for Asthma Patients by Hospital Characteristics—A Five-Year Population-Based Analysis

Abstract: This study sets out to explore the relationship between hospital characteristics, asthma length of stay (LOS), and costs per discharge. The study adopts hospitalization data from the Taiwan National Health Insurance Research Database covering the period from 1997 to 2001. Study subjects were identified from the database by principal diagnosis of asthma or asthmatic bronchitis, with a total of 139,630 cases being included in the study. Multiple-regression analyses were performed to explore the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…The significant relationship between longer LOS and higher costs, as reported here, has also been previously documented 12 . Decreasing asthma‐specific LOS has been identified as a primary factor in the preservation of hospital resources and reduction of costs 5 .…”
Section: Discussionsupporting
confidence: 81%
“…The significant relationship between longer LOS and higher costs, as reported here, has also been previously documented 12 . Decreasing asthma‐specific LOS has been identified as a primary factor in the preservation of hospital resources and reduction of costs 5 .…”
Section: Discussionsupporting
confidence: 81%
“…Length of stay (LOS) and costs per discharge were studied from the Taiwan National Health Insurance Research Database covering the period from 1997 to 2001. [18] Study subjects were identified from the database by principal diagnosis of asthma or asthmatic bronchitis, with a total of 139,630 cases being included in the study. Multiple regression analyses were performed to explore the relationship between LOS, costs per discharge and hospital characteristics, adjusting for age, gender, and discharge status of patients, as well as complications or comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings should be viewed in light of the conclusions of a study conducted by Lin et al in Taiwan, which found that asthma patients admitted to medical centers had longer LOS and higher costs than those admitted to district hospitals. 24 However, this phenomenon may be partially explained by the tendency of medical centers to receive a relatively higher proportion of patients suffering from more serious illnesses than district hospitals. Although advanced adjustments were made in the present study for patients with preexisting comorbidi- ties and for inhospital complications, the administrative database is limited in its ability to account for differences in severity of ischemic heart disease among patients.…”
Section: Discussionmentioning
confidence: 92%